Game enhanced learning through ICTS, for the development of basic communication skills in first basic year students at Unidad Educativa Jose Benito Benitez San Andrés during the school year 2018-2019 - Andrade Hurtado, Anny Angeline (2019)
The English language from very remote times has been distinguished as our second language and it has had great hierarchy. Nowadays, the need arises because this learning is estimated within the teaching process of the students and even more at an early age where they are more likely to receive a new language and to display receptive and productive language skills. It should be considered that the use of methodologies not appropriate to the time in which we are living and traditional teachings, causes demotivation and, consequently, the loss of interest in the acquisition of this knowledge; it is for this reason that to use of recreational activities should be induced, applying ICTs, to motivate and develop communication skills in the teaching-learning process in students………